PENGARUH MODEL PEMBELAJARAN AKTIF TIPE TEAM QUIZ TERHADAP MINAT BELAJAR MATEMATIKA SISWA DI KELAS VIII SMP NEGERI 3 BUKITTINGGI - Hidayatul Husna Syafitri; Aniswita (STKIP Subang, 2026)
The low level of mathematics learning interest among eighth-grade students at SMP Negeri 3 Bukittinggi has resulted in less optimal learning outcomes. One effort to address this problem is by implementing the Team Quiz active learning model, which actively engages students through group quiz activities, thereby encouraging healthy competition, collaboration, and active participation in mathematics learning. This study aimed to determine the effect of the Team Quiz active learning model on the mathematics learning interest of eighth-grade students at SMP Negeri 3 Bukittinggi.This study employed a quantitative approach using a pre-experimental design with a one-group pretest-posttest design. The population consisted of all eighth-grade students at SMP Negeri 3 Bukittinggi, totaling 155 students. The sample was selected using a random sampling technique, resulting in Class VIII.4 as the experimental class, consisting of 32 students. The research instrument was a mathematics learning interest questionnaire that had been tested for validity and reliability. The data were analyzed using the paired-samples t-test. The results indicated that both the pretest and posttest data were normally distributed and homogeneous. The hypothesis testing using the paired-samples t- test showed that the calculated t-value was 5.801, which was greater than the t- table value of 2.039 at the 0.05 significance level. These findings were supported by the SPSS analysis, which yielded a significance value of 0.000 (p < 0.05). Therefore, it can be concluded that the implementation of the Team Quiz active learning model had a significant effect on the mathematics learning interest of eighth-grade students at SMP Negeri 3 Bukittinggi.